1988
DOI: 10.1111/j.1471-4159.1988.tb03020.x
|View full text |Cite
|
Sign up to set email alerts
|

Voltage‐Sensitive Calcium Channels in Differentiated Neuroblastoma × Glioma Hybrid (NG108–15) Cells: Characterization by Quin 2 Fluorescence

Abstract: Depolarization of differentiated neuroblastoma X glioma (NG108-15) cells with KCl (50 mM) or veratridine (50 microM) stimulated Ca2+ accumulation, was detected by quin 2 fluorescence. Intracellular Ca2+ concentrations ([Ca2+]i) were elevated about threefold from 159 +/- 7 to 595 +/- 52 nM (n = 12). Ca2+ entry evoked by high extracellular K+ concentration ([K+]o) was voltage-dependent and enhanced by the dihydropyridine agonists, BAY K 8644 and CGP 28 392, in a dose-dependent manner. CGP 28 392 was less potent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
12
1

Year Published

1992
1992
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 43 publications
5
12
1
Order By: Relevance
“…To evaluate whether voltagegated Ca 2ϩ channels might represent an additional route for Ca 2ϩ -mediated regulation of PDE1A in 1321N1 cells, we looked for Ca 2ϩ influx in the presence of depolarizing concentrations of KCl (20 -60 mM). Not even the highest concentration of KCl could trigger Ca 2ϩ entry (data not shown), which concurs with the reported absence of voltage-gated Ca 2ϩ entry channels in 1321N1 cells (43,44). Therefore, this issue cannot be resolved with this model system.…”
Section: Cch Mediates a Casupporting
confidence: 82%
“…To evaluate whether voltagegated Ca 2ϩ channels might represent an additional route for Ca 2ϩ -mediated regulation of PDE1A in 1321N1 cells, we looked for Ca 2ϩ influx in the presence of depolarizing concentrations of KCl (20 -60 mM). Not even the highest concentration of KCl could trigger Ca 2ϩ entry (data not shown), which concurs with the reported absence of voltage-gated Ca 2ϩ entry channels in 1321N1 cells (43,44). Therefore, this issue cannot be resolved with this model system.…”
Section: Cch Mediates a Casupporting
confidence: 82%
“…We observed that the Ca agonists Bay, YC and CGP have little enhancing effect on basal 45Ca uptake by Bt2 cAMP-treated and untreated NG108-15 cells under non depolarizing conditions (5 mM KC1, data not shown), as observed previously (6,7,9). Our observations suggest that the enhancing effect on KCI-stimulated 45Ca uptake in differentiated NG108-15 cells was voltage-dependent.…”
supporting
confidence: 70%
“…Therefore, the present report describes the systematic study of the enhancing effects of these Ca agonists. Our results for Bay and CGP were more similar to those of Noronha-Blob et al (7) than to those of Freedman and Miller (6), since Noronha-Blob et al (7) observed that Bay is more potent than CGP in terms of enhancement rate and ED50 value for 45Ca up take. These differing reports may be a function of the differing reaction times adopted for the 45Ca uptake.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…[5][6][7][8][9][10] Voltage-sensitive sodium channels (VSSCs) have been existed not only in neuron, cardiac and skeletal muscle, but also in a variety of hormone secretory cells. VSSCs play a critical role in controlling the electrical excitability of animal cells, being primarily responsible for the rising phase of the action potential.…”
mentioning
confidence: 99%